2005
DOI: 10.1107/s1600536805019938
|View full text |Cite
|
Sign up to set email alerts
|

4-[(4-Hydroxy-3-methoxybenzylidene)amino]-1,5-dimethyl-2-phenylpyrazolidin-3-one

Abstract: The title compound, C19H19N3O3, was prepared from 4‐hydr­oxy‐3‐methoxy­benzaldehyde and 4‐amino‐1,5‐dimeth­yl‐2‐phenyl­pyrazolidin‐3‐one. The crystal structure shows that the molecules associate via intermolecular hydrogen bonds to form a supramolecular structure with a zigzag pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…deviation of fitted atoms of 0.0108 Å , and the dihedral angle with the central system is 4.82 (6) . These values are in agreement with those in a similar system (Diao et al, 2005). It is noted that the water molecules interact with pyrazolone molecules through hydrogen bonds (Table 1), which contribute to the stability of the structure in the solid state ( Fig.…”
Section: Commentsupporting
confidence: 91%
“…deviation of fitted atoms of 0.0108 Å , and the dihedral angle with the central system is 4.82 (6) . These values are in agreement with those in a similar system (Diao et al, 2005). It is noted that the water molecules interact with pyrazolone molecules through hydrogen bonds (Table 1), which contribute to the stability of the structure in the solid state ( Fig.…”
Section: Commentsupporting
confidence: 91%
“…Data collection: SMART (Bruker, 1999); cell refinement: SAINT (Bruker, 1999); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 1997a); program(s) used to refine structure: SHELXL97 (Sheldrick, 1997a); molecular graphics: SHELXTL (Sheldrick, 1997b); software used to prepare material for publication: SHELXTL. Schiff base ligands derived from 4-aminoantipyrine, such as thenoyltrifluoroacetone and 4-hydroxy-3-methoxybenzaldehyde, have been reported (Yu et al, 2002;Diao et al, 2005), which show the synthesis and crystal structure. In the present study, we report the synthesis and structure of the title compound, (I).…”
Section: Cl1-c2mentioning
confidence: 99%
“…Important to the understanding of the coordination potential of these ligands is a knowledge of the ligand structure. Accordingly, the synthesis and crystal structures of Schiff base ligands derived from 4-aminoantipyrine, such as thenoyltrifluoroacetone (Yu et al, 2002), 4-hydroxy-3-methoxybenzaldehyde (Diao et al, 2005) and 2,4-dichlorobenzaldehyde (Jing et al, 2005), have been reported.…”
Section: Data Collectionmentioning
confidence: 99%